Collecting and conserving of plant genetic resources ( Ex Situ Conservation ) (Journal of Humanitarian and Applied Sciences, 2023)
Plant genetic resources are playing an important role in human life for its relation to food, clothing and medicine. Libya has different ecosystems affected with Mediterranean climate, which is mild in the North and desert effect in the South, and dry, semi-dry conditions in between. This different climatic conditions have significant influence on the distribution of the plant genetic resources all over the country, which includes rangeland plants, forest trees and shrubs besides the medicinal and aromatic plants. The total number of these genotypes reached about 2150 genotypes, from which 300 are cultivated , 1850 of wild genotypes and 500 ornamental and other industrial genotypes. As other countries in the region , Libya has subjected to big influences due to climatic and ecological changes; rainfall averages were in all regions in the country including the natural. To reduce the effect of this dangerous situation, Libyan government has established the “Plant Genetic Resource Bank ” to conserve and secure the plant genetic resources from deterioration and extinction; to make it available for research and study in the field of genetic improvement and investment in economic importance programs. The national plant genetic resources bank has tackled in the last few years , many collection tours in different ecosystems to collect seeds of some rangelands, landraces and other economic important plants. The collected seeds were kept in the conservation room after cleaning, drying and viability testing. A herbarium also was established to keep plans specimens for plant identification. All plant climatic and geographic information were kept in special database program for the Gene bank (Libya Database System)
Keywords: plant Genetic Resources; Ex Situ Conservation; National Libya Gene bank,; Herbarium; Plant Genetic Resources; Active collection; Base collection